Diffuse Alveolar Hemorrhage in Patients with Systemic Lupus Erythematosus: A Single Center Retrospective Study in Malaysia - Piem Jie Leong; Anna Farazilah Mohd Salleh (Journal of Clinical Rheumatology and Immunology)
Background: The objective of this study was to evaluate demographic characteristics, clinical presentation, laboratory findings, treatments, and their impact on the outcome of systemic lupus erythematosus (SLE)-related diffuse alveolar hemorrhage (DAH) in our local setting. Methods: A total of seven patients were selected from our hospital’s local SLE database between 2013 and 2024 based on the inclusion criteria. Various variables were captured and analyzed using the Mann-Whitney [Formula: see text] test or Fisher’s exact test for comparison where appropriate. Results: All seven patients were female, with a median age of 26 years, and the median duration of SLE before DAH was 3 months. More than half were presented with all three symptoms: fever (57%), dyspnea (71.4%), and hemoptysis (85.7%). Kidney involvement was present in all cases. All patients received methylprednisolone as initial treatment with 71.4% subsequently received plasmapheresis, 57% received cyclophosphamide, 28.6% received intravenous immunoglobulin, and 14.3% received rituximab. Five out of the seven patients required invasive mechanical ventilation. The mortality rate was 57%. Two out of three survivors received a combination of multiple immunosuppressive agents. Non-survivors had significantly higher acute physiology and chronic health evaluation II (APACHE II) scores ([Formula: see text] = 0.034), while other variables were not statistically linked to mortality. In spite of that, all patients with nosocomial infection did not survive. Conclusion: Our observational study showed that a higher APACHE-II score was associated with a higher mortality rate. The efficacy of these treatment modalities cannot be conclusively determined due to the small sample size of this study. However, a combination of multiple immunosuppressive agents appeared to be associated with better outcomes in some patients.